GULASEKARAM, Pratheepan; RAMAKRISHNAN, Karthick S. The new immigration federalism. New York: Cambridge University Press, 2015. - Botelho Bevilacqua, Roberta Maria (Conjuntura Global, 2019)
Resenha crítica do livro "The new immigration federalism" (2015).